Determination of Gallium in Fly Ash by Inductively Coupled Plasma Atomic Emission Spectrometry - Liu, Bingbing; Han, Mei; Jia, Na; Wang, Yingbin (Asian Journal of Chemistry, 2015)
The content of gallium in fly ash was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES). Three acids (HNO3, HF, HClO4) were used for the pretreatment of samples. RF power and carrier gas flow of ICP spectrometer were optimized. The effects of the analytical line of gallium, the amount of nitric acid and hydrofluoric acid and dissolution temperature of samples on analytical results were investigated. The detection limit of the method was 0.58 μg/g and its relative standard deviation (RSD) was 3.85 % with good precision. The recovery of this method was 94.45-105.4 %, which met the requirements of sample analysis and further validated the reliability of the method.